Pengaruh Kepemimpinan Kepala Sekolah dalam Pengembangan Manajemen Strategik di SD Negeri 106813 - Simangunsong, Arimbi Syahkila; Azhima Sirait, Fauzan; Apriani Harahap, Tri Suci; Sahrani Sibarani, Wardah; Rafsanjani, Akbar; Muhklasin, Ahmad (Indo-MathEdu Intellectuals Journal, 2023)
The role of the school principal in quality development education is one of transformative leadership. Educational leaders who can effectively communicate a compelling vision for learning innovation and foster a cooperative and inclusive school culture can inspire collaboration among educators, students, and other stakeholders, leading to the advancement of educational strategic management. This study intends to examine the leadership role of school principals in creating strategies and policies that support improving educational standards, as well as the obstacles and difficulties faced by school principals when implementing development programs. In addition, this research will look at how the principal's leadership influences teacher involvement and participation in efforts to improve the level of education at SD Negeri 106813. The case study at SD Negeri 106813 was approached qualitatively in this research, interviews, observations, and document analysis were used to collect data. Research findings show that the head's leadership in developing strategies and policies aimed at improving the quality of education at SD Negeri 106813 is an important function of the school. A school principal must be fully committed to improving educational standards in the school and can develop workable solutions